Externalities in wild pig damages on U.S. crop and livestock farms: The role of landowner actions and landscape heterogeneity - Sophie C. McKee; Nathan D. DeLay; Daniel F. Mooney; Stephanie A. Shwiff (PLoS ONE, 2025)
Invasive wild pigs can impose significant economic costs on crop and livestock farms. Many factors influence the incidence and intensity of these losses, making efforts to reduce or eradicate these populations complex. While farm and ranch operators may perceive wild pigs as agricultural pests, other landowners often see them as wild game with recreational value. This study investigates the relationship between landowner practices that attract wild pigs and the likelihood of pig presence and damage on farm and ranch operations. It considers the farmers’ own actions that attract wildlife, neighboring landowner actions, the heterogeneity of the surrounding landscape, and county-level factors. The findings show a significant and positive associations between neighbors’ actions and the probability of wild pig presence and financial losses from wild pig damage. Additionally, increasingly heterogeneous landscapes may further exacerbate this challenge. This research indicates that the choices made by adjacent property owners can undermine the effectiveness of public and private efforts to manage wild pig populations. Conversely, the impacts of wild pig management likely extend beyond specific management areas. Holistic eradication or population control programs should consider these externalities to adequately and efficiently address their impacts.